2000
DOI: 10.1177/107110070002100203
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Tarsi Approach with Trans-articular Fixation for Displaced Intra-articular Fractures of the Calcaneus

Abstract: The charts and radiographs of 99 patients with 106 intraarticular fractures of the calcaneus were retrospectively reviewed. There were 75 men and 24 women. The average age was forty-two (range, 17 to 81). Fifty-seven of the fractures were left and 49 were right. The mechanism of injury was a fall from a height in 69 patients and motor vehicle accident in 30 patients. According to Sanders classification, seventy-one cases (67%) had type II fractures, 25 cases (23.6%) had type III, and ten cases (9.4%) had type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 26 publications
6
77
0
5
Order By: Relevance
“…Frequently, there is no correlation between the angle and functional results of treatment [7,11,37,38]. Correlations between the crucial angle, as described by Gissane, and the final outcome were never found [11,20,38].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Frequently, there is no correlation between the angle and functional results of treatment [7,11,37,38]. Correlations between the crucial angle, as described by Gissane, and the final outcome were never found [11,20,38].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies found correlations with the outcome and measurements of Böhler's angle, usually with extremes of Böhler's angle or when division of Böhler's angle into three groups was applied ("less than zero degrees", "zero to 15°" and "16°or higher") [33][34][35][36]. Frequently, there is no correlation between the angle and functional results of treatment [7,11,37,38]. Correlations between the crucial angle, as described by Gissane, and the final outcome were never found [11,20,38].…”
Section: Discussionmentioning
confidence: 99%
“…, 둘째는 관절경을 이용하는 방법 6,14) , 셋째는 외고정 장치를 이용하는 방법이다 10,12,15) . 짧은 절개를 이용하는 방법은 족근동에서 거골하 관절을 따라서 절개를 하거나 4,7,8) 아킬레스건의 외측연을 따라서 종절개를 하는 방법 13) 으로 크게 구분할 수 있다. 짧은 절 개를 하면 후방 관절면의 외측 관절면을 포함하는 골절편 의 전위를 육안적으로 보고 정복할 수 있다는 것이 장점이 지만 전체적인 윤곽이나 관절면 이외의 부분은 경피적으로 정복하고 고정해야 한다.…”
Section: 서 론unclassified
“…Fernandes (35) relatou sua experiência com 38 casos, todos tratados cirurgicamente com a via de acesso pelo seio do tarso, tendo três casos (7,89%) de sofrimento tecidual superficial. Ebraheim et al (36) avaliaram o resultado obtido pela via curta em 99 pacientes (106 pés), tendo apenas quatro casos (3,8%) de infecção superficial e um caso (0,9%) de infecção profunda. Avaliaram a vantagem da via em abordar diretamente a faceta posterior e o aspecto anterior e lateral, tendo como limitação a redução indireta da tuberosidade posterior e do sustentáculo do tálus.…”
Section: Tabela 4 -Comparação Entre As Médias Dos Valores Máximos Dosunclassified